1982
DOI: 10.1152/jappl.1982.53.6.1572
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic contribution to heart rate recovery from exercise in humans

Abstract: To assess the contribution of the autonomic nervous system to heart rate recovery following exertion, heart rate was observed after peak treadmill exercise in six men following parasympathetic blockade (PB) with atropine sulfate (0.03 mg/kg), sympathetic blockade (SB) with propranolol hydrochloride (0.20 mg/kg), double blockade (DB) with both drugs, and no drugs (ND). Least-squares analysis of each subject's heart rate (HR) as an exponential function of recovery time (t) was computed for each treatment giving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
192
0
9

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(204 citation statements)
references
References 0 publications
3
192
0
9
Order By: Relevance
“…An increase in vagal activation as well as a decrease in sympathetic activation has been detected already during the first minutes of the recovery (Savin et al 1982). It has been suggested that the immediate first minute decline in HR after exercise cessation is mainly vagal in origin (Arai et al 1989;Imai et al 1994;Perini et al 1989;Savin et al 1982), although the relative role of sympathetic and vagal divisions seems to depend on exercise intensity (Imai et al 1994;Perini et al 1989). The recovery of heart rate has widely been investigated in clinical studies, and its prognostic value in different heart diseases has been confirmed.…”
Section: Heart Rate and Hrv During Recovery After Exercisementioning
confidence: 99%
“…An increase in vagal activation as well as a decrease in sympathetic activation has been detected already during the first minutes of the recovery (Savin et al 1982). It has been suggested that the immediate first minute decline in HR after exercise cessation is mainly vagal in origin (Arai et al 1989;Imai et al 1994;Perini et al 1989;Savin et al 1982), although the relative role of sympathetic and vagal divisions seems to depend on exercise intensity (Imai et al 1994;Perini et al 1989). The recovery of heart rate has widely been investigated in clinical studies, and its prognostic value in different heart diseases has been confirmed.…”
Section: Heart Rate and Hrv During Recovery After Exercisementioning
confidence: 99%
“…3 This improvement has been associated with various internal physiological adjustments in such a way that a lower heart rate in the recovery phase would be due to decreased venous return and systemic needs. 4 The increase in heart rate in response to exercise is accompanied by a reduction in vagal tone that is further increased over basal level after exercise has ended 5 through the activation of the autonomic nervous system immediately after cessation of maximum activity. 6 In addition to its use to evaluate physical condition, heart rate recovery (HRR) from maximal exercise in the first few minutes after ceasing the activity is also a valid indicator of risk of sudden death during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Slower changes in the stimuli to metaboreceptors and baroreceptors accompanying clearance of metabolites and delayed elimination of body heat and catecholamines are thought to be other factors contributing to heart rate recovery after physical activity. Nevertheless, parasympathetic activation is considered to be the main mechanism underlying exponential cardiodeceleration after exercise (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%